Metabolic syndrome in type 1 diabetes: higher time above range and glycemic variability revealed by continuous glucose monitoring (CGM) - Yayu Fang; Wei Liu; Xiaoling Cai; Yu Zhu; Mingxia Zhang; Siqian Gong; Xiangqing Wang; Chu Lin; Rui Zhang; Sai Yin; Juan Li; Yongran Huo; et al. (Diabetology & Metabolic Syndrome)
Abstract Aims To investigate the glucose profile of Chinese individuals with type 1 diabetes (T1D) who also have metabolic syndrome. Materials and methods Type 1 diabetes participants from Peking University People’s Hospital were recruited from Jan 2017 to Jan 2024. The diagnosis of metabolic syndrome was developed based on the updated National Cholesterol Education Program Adult Treatment Panel III (NCEP-ATPIII) criteria. Demographic data, anthropometric measurements, clinical information and continuous glucose monitoring (CGM) data were collected and compared between participants with metabolic syndrome and those without. Results The median age of the participants was 50.0 years (IQR 35.0-63.3), and the median duration was 10.0 years (IQR 2.0–17.0). Compared to those without metabolic syndrome, participants with metabolic syndrome were older (63.0 years, IQR 41.0–69.0 vs. 48.5 years, IQR 35.0–60.0; P < 0.001) and had a longer duration (13.0 years, IQR 5.0–22.0 vs. 9.0 years, IQR 2.0–15.0; P = 0.011). The comparison of CGM metrics suggested significantly higher time above range (TAR, 48.9%, IQR 35.3–59.5 vs. 32.8%, IQR 16.1–47.6; P < 0.001), standard deviation (SD, 3.6 ± 0.9 mmol/L vs. 3.2 ± 1.0 mmol/L; P = 0.022) and interquartile range (IQR, 4.2 mmol/L, IQR 3.2–4.8 vs. 3.7 mmol/L, IQR 3.0-4.5; P = 0.046) in those with metabolic syndrome. And the Logistic regression analysis showed that TAR (OR 1.53, 95% CI 1.02–2.23, per 20% increase), SD ( OR 1.75, 95% CI 1.07–2.84, P = 0.025) and IQR (OR 1.50, 95% CI 1.03–2.19, P = 0.036) were positively associated with metabolic syndrome after adjusting for age, sex, diabetes duration, BMI and complication status. Conclusions Our findings suggested that in T1D participants, metabolic syndrome was associated with higher glucose level and glycemic variability. Personalized diabetes education including optimal meal planning and sufficient physical activity should be emphasized to improve glycemic control in T1D with metabolic syndrome.